Quo Vadis Honorary Council of the Constitutional Court in Enforcing the Idea of ​​Constitutional Ethics for Constitutional Judges in Indonesia - Feiruz Rachmita Alamsyah; Martitah Martitah (Universitas Negeri Semarang, 2024)
The oversight is carried out by the Ethics Council and MKMK, where the Ethics Council is responsible for enforcing breaches of the code of ethics and maintaining the dignity and integrity court. The existence of the Ethics Council is currently in a status quo, seemingly in a state of limbo because, on the one hand, the Constitutional Court has legally explained that the enactment of Law No. 7 of 2020 marks the end of the Ethics Council's existence. On the other hand, PMK No. 2 of 2014, which serves as a guideline for the supervision of the Ethics Council, has not yet been revoked by a new PMK. As a result, the mechanism for overseeing the code of ethics for Constitutional Court judges is in a vacuum and cannot function effectively. Attempts to explain how the oversight of the MKMK is viewed from both a historical and practical perspective within Indonesia's constitutional system. It then compares it with other countries and examines the issues surrounding the implementation of oversight over the Ethics Council and MKMK, effectively enforce the code of ethics for judges, and how the oversight mechanisms interact with descriptive-qualitative methods. The findings are numerous, including the ineffectiveness in handling ethical cases because no authority has been delegated to the Ethics Council, and MKMK is formed on an ad hoc basis. The creation of PMK for the formation of the Ethics Council is affected by conflicts of interest, and passive oversight by Constitutional Court judges occurs because the Ethics Council examines allegations of code of ethics violations based on reports from the public. Therefore, the author proposes a normative reformulation to restore the role of Judicial Commission as the external overseer of the Constitutional Court to maintain and enforce the honor, dignity, and proper conduct of Constitutional Court judges.